The Efficacy and Safety of Bisphosphonates for Osteoporosis in Women Older Than 65 Years: A Meta-Analysis - Fan, Qin; Wang, Junjie (Current Pharmaceutical Design, 2020)
Background: Osteoporosis presents a major threat to the health of women older than 65 years. Bisphosphonates (BPs) are now the principal class of medications for osteoporosis. Objective: To evaluate the efficacy and safety of BPs in women older than 65 years. Methods: A comprehensive search in the PubMed, EMBASE, Web of Science and Cochrane Central databases was undertaken for randomized controlled trials (RCTs) on the efficacy and safety of BPs in women older than 65 years. The primary outcome measures were the change in bone mass density (BMD), serum bone turnover marker levels, fracture rate and the adverse effect (AE) rate. The final search was performed in August 2019. Results: Seven RCTs were included. A total of 23287 patients met the inclusion criteria. BPs significantly increased the BMD of the posteroanterior (PA) spine, lateral spine and femoral neck, and reduced the fracture, vertebrate fracture and hip fracture rates in women older than 65 years. In addition, BPs increased the risks for pyrexia, myalgia, arthralgia, headache and influenza-like symptoms and had no statistical effect on any AEs, any serious AEs, discontinuation due to AEs, oesophagitis, any upper gastrointestinal adverse event, atrial fibrillation and myocardial infarction occurrence in women older than 65 years. Finally, intravenous BPs reduced hip fracture risk but increased AEs in women older than 65 years. Conclusion: Despite the fact that AEs significantly increased after drug delivery, BPs are highly effective and safe for managing osteoporosis in women older than 65 years. Zoledronic acid caused an increased rate of AEs in women older than 65 years, but these AEs seemed to be mild to moderate. In addition, the hip fracture rate in women older than 80 years old treated with BPs was different than that in the other included patients. Therefore, doctors may prescribe BPs for women older than 65 years in order to increase BMD, and AEs and hip fractures in women older than 80 years should be given attention.
Keywords: Osteoporosis